Green Synthesis of Ag and Pd Nanospheres, Nanowires, and Nanorods Using Vitamin B2: Catalytic Polymerisation of Aniline and Pyrrole. (10th December 2007) - Nadagouda, Mallikarjuna N.; Varma, Rajender S.
Abstract : For the first time, we report green chemistry approach using vitaminB 2 in the synthesis of silver (Ag) and palladium (Pd), nanospheres, nanowires, and nanorods at room temperature without using any harmful reducing agents, such as sodium borohydride (NaBH 4 ) or hydroxylamine hydrochloride and any special capping or dispersing agent. VitaminB 2 was used as reducing agent as well as capping agent due to its high-water solubility, biodegradability, and low-toxicity compared with other reducing agents. The average particle size of nanoprticle was found to be Ag (average size 6.1± 0.1 nm) and Pd (average size 4.1± 0.1 nm) nanoparticles in ethylene glycol and Ag (average size 5.9± 0.1 nm, and average size 6.1± 0.1) nanoparticles in acetic acid and NMP, respectively. The formation of noble multiple shape nanostructures and their self assembly were dependent on the solvent employed for the preparation. When water was used as solvent media, Ag and Pd nanoparticles started to self-assemble into rod-like structures and in isopropanol Ag and Pd nanoparticles yielded wire-like structures with a thickness in the range of 10 to 20 nm and several hundred microns in length. In acetone and acetonitrile medium, the Ag and Pd nanoparticles are self-assembled into a regular pattern making nanorod structures with thicknesses ranging from 100 to 200 nm and lengths of a few microns. The so-synthesized nanostructures were characterized using scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy dispersive X-ray (EDX) analysis, and UV spectroscopy. The ensuing Ag and Pd nanoparticles catalyzed the reactions of aniline and pyrrole to generate polyaniline and polypyrrole nanofibers and may find various technological and biological applications. This single-step greener approach is general and can be extended to other noble metals and transition metal oxides.